Nueva evidencia sobre la relación entre riesgo Argentino y actividad económica 1986-2019 - Jorge C. Ávila (Universidad del Centro de Estudios Macroeconómicos de Argentina (UCEMA), 2021)
– Between 1986 and 2003 the Argentine risk premium was able to explain, almost alone, the Argentine business cycle. As time went by, the premium lost gradually its explanatory power till losing it all between 2011 and 2019. Meanwhile, a huge increase in public expenditure might have triggered a regime change. We investigate the loss of explanatory power of the Argentine premium and the emergence of the terms of trade and public expenditure as additional explanatory variables of the business cycle. And we attempt to answer two questions: why did the premium lose its power? and why did the Argentine economy stagnate between 2011 and 2019?
Keywords: E32; 330; Konjunkturforschung; Länderrisiko; Terms of Trade; Öffentliche Ausgaben; Argentinien